2020
DOI: 10.1515/ntrev-2020-0038
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nanoparticles on engineering performance of cementitious composites reinforced with PVA fibers

Abstract: AbstractIn this study, the influence of nano-CaCO3 (NC) and nano-SiO2 (NS) on engineering properties of cementitious composites reinforced with polyvinyl alcohol (PVA) fibers was investigated including slump and fracture properties as well as compressive, flexural, tensile, and strengths. The influence mechanism of NS content on properties of cementitious composites was revealed. The combined effects of NS and NC were evaluated on the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…Zhang and Ling et al found that adding 0–1.5% nanosilica particles was optimal for enhancing the compressive strength, flexural strength, and fracture energies of reinforced concrete with polyvinyl alcohol fibers. Moreover, 2.5% nanosilica particles was found to be the best for tensile strength; nevertheless, when the content was greater than 2%, the NS was prone to self-desiccation and flocking together, leading to micro cracks and strength losses in the composite [ 21 , 22 ]. According to the experimental results from most researchers on concrete with the addition of NS, it can be concluded that low doses of NS can significantly enhance the mechanical properties of concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang and Ling et al found that adding 0–1.5% nanosilica particles was optimal for enhancing the compressive strength, flexural strength, and fracture energies of reinforced concrete with polyvinyl alcohol fibers. Moreover, 2.5% nanosilica particles was found to be the best for tensile strength; nevertheless, when the content was greater than 2%, the NS was prone to self-desiccation and flocking together, leading to micro cracks and strength losses in the composite [ 21 , 22 ]. According to the experimental results from most researchers on concrete with the addition of NS, it can be concluded that low doses of NS can significantly enhance the mechanical properties of concrete.…”
Section: Introductionmentioning
confidence: 99%
“…When the nano-SiO 2 content varied from 0 to 1.5%, the fracture energy, initiation, and unstable fracture toughness marginally rose, however, they decreased when the nano-SiO 2 content was higher than 1.5%. 30 Due to the strong relationship between the mechanical and biological properties of scaffolds, these approaches have had a significant impact. Cell adhesion, proliferation, and differentiation can all be impacted by the mechanical qualities of the scaffolds.…”
Section: Resultsmentioning
confidence: 99%
“…In comparison to the composite containing the same amount of nano-SiO 2 , the composite including NC had lower strengths. When the nano-SiO 2 content varied from 0 to 1.5%, the fracture energy, initiation, and unstable fracture toughness marginally rose, however, they decreased when the nano-SiO 2 content was higher than 1.5% . Due to the strong relationship between the mechanical and biological properties of scaffolds, these approaches have had a significant impact.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al [26] found that the fiber volume should not be more than 2% to ensure good performance in ECC blends. Due to their composite performance and economic considerations, PVA fibers are among the types of fibers used by ECC and the other high performance cementitious composites [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%